Effects of steam pretreated rice biomass condensate containing soluble solid inhibitors on disruption of Pomacea canaliculata egg - Khamis, Nor Azahanim; Shamsudin, Saleha; Zabidi, Muhammad Hafiz; Kasim, Khairul Farihan; Bahrin, Ezyana Kamal (Penerbit Universiti Malaysia Perlis, 2023)
Pomacea canaliculata is an invasive freshwater snail species that has become a serious pest of rice in irrigation and paddy fields and is popularly known as the golden apple snail. They are species that are capable of surviving and spreading rapidly, causing significant changes in the ecosystem. The application of natural by-products of a physicochemical method of biomass steam pre-treated condensate is one option for disrupting Pomacea Canaliculata egg. This experiment was conducted to investigate the feasibility of steam pre-treated rice biomass condensate which contained soluble solid inhibitors as a biopesticide to eradicate Pomacea canaliculata. Rice straw, rice husk, and a combination of rice straw and rice husk (1:1) were pre-treated by the saturated steam pre-treatment in a batch reactor at high temperatures (190°C and 210°C) for 10 min. The steam condensate produced from this system was analysed for major degraded products or inhibitors such as furfural, hydroxymethylfurfural (HMF), and phenol. The steam condensate which contained soluble solid inhibitors was then analysed for solubility test on P. canaliculata eggs. The effect of soluble solid inhibitors on the eggs was structurally examined by using a scanning electron microscope (SEM). The results revealed that rice husk which was pre-treated at 210°C reflected the highest contents of furfural (0.300 g/L), HMF (1.670 g/L), and phenol (0.087 g/L). However, the combination of rice biomass sample (1:1) condensate at 210°C demonstrated the greatest solubility percentage (11.51%) when treated to the eggs P. canaliculata eggs. The image of the egg structure examined by SEM clearly displayed the fractures forming on the cuticle layer of the eggs. SEM results demonstrated that the condensate from saturated steam pre-treated rice biomass has the possibility to be used as a biopesticide to disrupt the eggs and eventually could prevent the snails’ invasion.